Hydrodynamic characteristics of a hybrid oscillating water column-oscillating buoy wave energy converter integrated into a π-type floating breakwater. (June 2022) - Cheng, Yong; Du, Weiming; Dai, Saishuai; Ji, Chunyan; Collu, Maurizio; Cocard, Margot; Cui, Lin; Yuan, Zhiming; Incecik, Atilla
Abstract: Combining multiple-types of Wave Energy Converters (WECs) and integrating them into in-development or pre-existing marine platforms can reduce the total Levelised Cost of Energy (LCoE) by sharing infrastructures and maintenance costs. The current study proposes an innovative multi-purpose solution by deploying an Oscillating Buoy (OB) device inside the chamber of an Oscillating Water Column (OWC) WEC integrated into a π-type floating breakwater. A fully non-linear time-domain model based on the Higher-Oder Boundary Element Method (HOBEM) is established to investigate the hydrodynamic performance of the proposed concept. The non-linear time-domain model is generalised to incorporate the OWC (aero and hydrodynamics coupling) and multi-body interaction. A series of simulations are performed to examine the hydrodynamic performance of the proposed hybrid concept. Results were compared with an isolated breakwater and an OWC-integrated breakwater, demonstrating that the proposed hybrid concept has a beneficial impact on both wave energy conversion and transmitted wave attenuation. In addition, long-period waves enter into the chamber more easily, which leads to a larger inner water motion and pressure fluctuation in the chamber. Importantly, there exists a coupled resonant motion between the OB device and the water surface in the chamber, which enhances the maximum capture efficiency and the efficiency frequency bandwidth. The asymmetric OB with a triangle-shaped bottom is found to absorb the wave energy along with the water depth more effectively. Despite the better performance, the current design does not increase the characteristic system volume and has no external moving part, making it ideal for array deployment. Highlights: A hybrid OWC-OB WEC integrated into a π-type floating breakwater, is proposed. The introduction of the OB enhances wave energy conversion in long-period waves. There exists a coupled resonant motion between the OB and the water surface in the chamber. The asymmetric OB effectively interacts with inner waves and compress interior airflow. The synergistic benefits between wave attenuation and energy extraction are shown.